PEMANFAATAN SALURAN DRAINASE SEBAGAI RUANG HIJAU TERBATAS DI KAMPUS A UNIVERSITAS NEGERI JAKARTA - Guntur Wisnu Gumelar; Henita Rahmayanti; Daryati Daryati (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2019)
The potential negative impacts include being one of the factors causing flooding,being a disease-causing vector habitat and providing an unfavorable visual appearance. On the otherhand, the development that took place on Campus A UNJ has reduced the area of green space.Development needs to pay attention to environmental elements as a form of implementation ofSustainable Development which aims to maintain environmental quality and support the activities ofcitizens. For this reason, research is carried out in an effort to maintain drainage channels whileincreasing green space and adding environmental aesthetics.Planning is carried out on open drainage channels on Campus A UNJ. Planning is done bymeans of literature study, identifying the characteristics of physical and biological aspects, analyzingthe potential and constraints on the site and making a design with a retotive approach.The results of the study obtained drainage channels that can be utilized along 1182.08 m.Tread width that can be used as a green space construction is only 60 cm. The additional effectivegreen space obtained is 292.82 m². Drainage channels are made by Manhole with a size of 50 cm x 60cm and 60 x 60 cm integrated with the construction of green spaces. Types of plants in the form offlowers and shrubs. The planting media used in the form of organic and inorganic media.